Trastornos de la articulación temporomandibular y su relación con la pérdida dentaria en los y las estudiantes de la Universidad Nacional de Loja, modalidad de estudios presencial durante el periodo mayo-julio 2014. - Masache Jadán, Marcia Tatiana (2014)
This thesis entitled "TMJ DISORDERS AND THEIR RELATIONSHIP WITH THE TOOTH LOSS AND STUDENTS OF NATIONAL UNIVERSITY OF LOJA, MODE STUDIES CLASSROOM DURING THE PERIOD MAY-JULY 2014" is an investigation from the approach of a general objective: to determine the frequency of TMJ disorders and its relation to tooth loss with their specific objectives: to establish the relationship between the frequency of TMJ disorders and frequency of tooth loss, know the dysfunction it occurs most frequently and gender distribution. Being a research scientist, descriptive and observational character develops through the assessment and inspection of the structures involved. To which the study was conducted on 894 students at the National University of Loja, of which it was found that 375 students had clinical TMJ; 48.8% of them have tooth loss, also occurs more frequently in females in a ratio of 2: 1. In the men's population. The main clinical sign of TMJ dysfunction is represented with the click joint which may be with or without pain. Concluding that tooth loss is directly related to the presence of TMJ disorders, causing displacement of teeth present in the mouth which causes premature contacts, changing the path of travel of the articular condyle to the fossa. Just as the loss of posterior oclusal support intrusion and producing condylar compression. Keywords: Disorders of TMJ, dysfunction, tooth loss.